In-hospital Cardiac Arrest in Patients With Sepsis: A National Cohort Study - Duazo, Catherine; Hsiung, Jo-Ching; Qian, Frank; Sherrod, Charles Fox; Ling, Dean-An; Wu, I-Ju; Hsu, Wan-Ting; Liu, Ye; Wei, Chen; Tehrani, Babak; Hsu, Tzu-Chun; Lee, Chien-Chang (Frontiers in Medicine, 2021)
BACKGROUND: Little is known about the risk of in-hospital cardiac arrest (IHCA) among patients with sepsis. We aimed to characterize the incidence and outcome of IHCA among patients with sepsis in a national database. We then determined the major risk factors associated with IHCA among sepsis patients. METHODS: We used data from a population-based cohort study based on the National Health Insurance Research Database of Taiwan (NHRID) between 2000 and 2013. We used Martin’s implementation that combined the explicit ICD-9 CM codes for sepsis and six major organ dysfunction categories. IHCA among sepsis patients was identified by the presence of cardiopulmonary resuscitation procedures. The survival impact was analyzed with the Cox proportional-hazards model using inverse probability of treatment weighting (IPTW). The risk factors were identified by logistic regression models with 10-folds cross validation, adjusting for competing risks. RESULTS: We identified a total of 20,022 patients with sepsis, among whom 2,168 developed in-hospital cardiac arrest. Sepsis patients with higher burden of comorbidities and organ dysfunction were more likely to develop in-hospital cardiac arrest. Acute respiratory failure, hematological dysfunction, renal dysfunction and hepatic dysfunction were associated with increased risk of IHCA. Regarding the source of infection, patients with respiratory tract infection were at the highest risk, whereas patients with urinary tract infections and primary bacteremia were less likely to develop IHCA. The risk of IHCA correlated well with age and revised cardiac risk index. The final competing risk model concluded that acute respiratory failure, male gender, and diabetes are the three strongest predictors for IHCA. The effect of IHCA on survival can last 1 year after hospital discharge, with an IPTW-weighted hazard ratio of 5.19 (95%CI: 5.06, 5.35) compared to patients who did not develop IHCA. CONCLUSION: IHCA in sepsis patients had a negative effect on both short and long term survival. Risk of IHCA among hospitalized sepsis patients was strongly correlated with age and cardiac risk index. The three identified risk factors can help clinicians to identify patients at higher risk for IHCA.